The Leadership Role Of An Effective School Principal - M. Hafiz Artasya; Bahtiar Siregar; Rizky Novianti; Luxvina Luxvina; Tengku Robi Awaludin Sani; Su’ad Naimah (Journal on Education, 2024)
This research was made with the aim of analyzing the leadership role of school principals in order to improve student academic success and the overall quality of education in an educational institution. The proceedings that the authors made this time were entitled The leadership role of effective school principals. On this occasion we as authors use the literature review method as material for making proceedings. The data obtained through google schoolar and sinta searches, collecting literature (material materials) sourced from books, journals and other sources with the keyword 'Principal Leadership. Leadership is essentially the ability of a person to foster, guide, direct and move others to work together to achieve the goals set by carrying out a series of activities including directing the people involved in an institution or organization that he leads. In addition, it is also able to combine the elements of an institution with the situation of its cultural environment, which is a condition in this case for the creation of an effective educational institution (school). Effective school principals are principals who have a balance as managers and leaders. Principal leadership plays a major role in directing schools towards educational excellence. With a clear vision and mission, principals can motivate students and teachers to achieve higher achievements.